Risk factors for Candida parapsilosis bloodstream infection in a neonatal intensive care unit: a case-control study. Issue 1 (January 2017) - Garzillo, Carmine; Bagattini, Maria; Bogdanović, Lidija; Di Popolo, Anna; Iula, Vita; Catania, Maria; Raimondi, Francesco; Triassi, Maria; Zarrilli, Raffaele
Abstract Background Candida parapsilosis is increasingly responsible for invasive candidiasis in neonates. This study investigates phenotypic and genotypic features ofC. parapsilosis microbial isolates and underlying clinical conditions associated with acquisition ofC. parapsilosis in a neonatal intensive care unit (NICU) in Italy. Methods Identification ofC. parapsilosis was performed by VITEK® 2 and MALDI TOF and confirmed by analysis of internal transcribed spacer ribosomal DNA sequences. Genotyping was performed by PCR fingerprinting. Antifungal susceptibility of strains was evaluated by microdilution. A case-control study was designed to identify risk factors forC. parapsilosis bloodstream infection. Results During the study period (April 2009- April 2012), C. parapsilosis was responsible for 6 umbilical catheter and 11 central catheter-associated bloodstream infection in 17 neonates in the NICU. Molecular typing identified identical fingerprinting profile in allC. parapsilosis isolates from neonates. Fifteen of 17C. parapsilosis isolates were susceptible to all antifungal drugs, two isolates were resistant to fluconazole and intermediate susceptible to itraconazole. Low birthweight, gestational age and time to exposure to assisted ventilation were risk factors forC. parapsilosis infection in neonates in the NICU at univariate and multivariate analysis. Conclusion C. parapsilosis bloodstream infections in the NICU were caused by a single epidemic clone. Low birthweight, gestational age and time to exposure to invasive devices, with predominance of assisted ventilation, were the clinical conditions associated withC. parapsilosis bloodstream infection in the NICU.